AB0670 Short and long-term treatment with infliximab in retinal vasculitis of behÇet's disease. multicenter study of 72 patients. (12th June 2018) - Martín-Varillas, J.L.; Calvo-Río, V.; Demetrio-Pablo, R.; Atienza-Mateo, B.; Loricera, J.; Hernández, M.V.; Adán, A.; Mesquida, M.; Peiteado, D.; Pato, E.; Díaz, D.; Martínez, L.; et al.
Abstract : Background: Retinal vasculitis (RV) is a serious complication of uveitis due to Behçet's disease (BD). 1–2 Objectives: We assess the short/long-term efficacy of Infliximab (IFX) in refractory RV of BD. Methods: Multicenter study of patients with RV of BD refractory to corticosteroids and at least 1 conventional immunosuppressant (IS). We compared efficacy of IFX between baseline, 1st week, 1–6 months and 1–6 years. Results: 72 patients/129 affected eyes (40♂/32♀) with mean age of 39.6±9.7 years. HLA-B51 was (+) in 63%. Before IFX onset, patients had received: oral/e.v. glucocorticoids (n=98), CyA (n=56), AZA (n=43), MTX (n=34) and other IS (n=22). IFX was used as monotherapy in 17 patients and combined with conventional IS in the remaining 55. IFX dose was as follows: 3 mg/kg/4–8 w (n=5), 4 mg/kg/4 w (n=1), 5–5.5 mg/kg/4–8 w (n=66). Following IFX onset, an improvement in RV was seen, as well as in the other ocular outcomes. This enhancement was maintained (table 1). After a mean follow-up of 26.5±22.1 months, IFX was discontinued in 44: remission (n=15), primary failure (n=16), preference of another route of administration (n=8), pregnancy (n=1) and adverse effects (n=4). Conclusions: IFX seems an effective short/long-term treatment in RV of BD. References: [1] Calvo-Río V, Blanco R, Beltrán E, et al. Anti-TNF-alfa therapy in patients with refractory uveitis due to Behçet's disease: a 1-year-follow-up study of 124 patients. Rheumatol. 2014; 53(12):2223–31 [2] Santos-Gómez M, Calvo-Río V, Blanco R, et al. The effect of biologic therapy different from infliximab or adalimumab in patients with refractory uveitis due to Behçet's disease: results of a multicentre open-label study. Clin Exp Rheumatol. 2016; 34 (6Suppl 102):S34-S40 Disclosure of Interest: None declared